Implementation of National Agricultural Market (eNAM): A Successful Case of APMC Nizamabad (Telangana) - Angadi, Sangamesh; C, Madhulatha; Shalendra (Journal of Agricultural Extension Management, 2024)
Indian agriculture has achieved impressive growth in terms of production which increased many fold since independence. However, challenge is to link this production efficiently with market. Realising the importance of market, the Government has taken various measures to make marketing system more efficient, responsive, liberal and infrastructure rich. National Agricultural Market (eNAM) is one such initiative which is a comprehensive marketing concept helping integration of exchange functions of a market with physical and facilitating functions under as a single window. Progress of the concept has been impressive with 1361 markets getting integrated with eNAM platform from 27 states/UTs. The concept has also seen introduction of initiatives like FPO Module to facilitate trade by farmers’ organisation, warehouse based trading, logistic module and Platform of Platform (POP). Telangana has emerged as a successful example in implementing eNAM capturing more than 10 percent of the all India users registered on the platform like traders, commission agents and farmers with proportionately less number of markets. APMC Nizamabad is a successful example with many lessons for other interest markets and states like shifting from manual auction to e-tendering for price discovery, alternative of direct sale platform available to farmers, optimal utilisation of facilities by creating extra gate entry points and digitisation of weighment process. Integration of services like storage and finance have made the Nizamabad market operate as a service unit. The Nizamabad Market suggest that the platform of eNAM can be leveraged for improving the efficiency of market and help it convert into a service unit.